Association of Body Condition Score with Lactation and Reproductive Performance in Murrah Cross Buffaloes in Chitwan, Nepal - Paudel, M; Gautam, G; Khatri, KB; Baral, P; Pantha, BP (Nepalese Veterinary Journal, 2023)
Body condition score (BCS) is a precise method for determining the stored energy reserves of dairy animals, which are located in the form of subcutaneous fat tissue, indicated by the animal’s degree of accomplished nutrition, and could be used as a management and selection tool to improve reproductive performance. The objective of this research was to investigate and quantify relationships between BCS and milk production, milk composition, and reproductive performance in Murrah cross buffalo. For this purpose, a semi-structured questionnaire was created and BCS was calculated using a visual technique based on a BCS chart. The sampling approach employed was a completely randomized design. A total of 165 Murrah cross buffaloes from 59 household farms were used in the study, where 130 milk samples were collected and used to assess the milk parameters by lacto-scan. Four BCS groups were namely 2.5-2.99, 3.0-3.49, 3.5-3.99, and 4.0-4.99 where the BCS score was found to grow during the dry period until calving, then decreased as milk production increased. BCS group (3.5-3.99) had higher performance during all the lactation periods with a peak milk yield of 11.4 ± 1.1 kg. At the late lactation stage BCS group (3.5-3.99) showed higher values of SNF (9.77), protein (4.01), and lactose (3.82), followed by BCS groups 4.0-4.49, 3.0-3.49, and 2.5-2.99. At the early, lactation stages, the BCS group (3.5-3.99) had the highest (P